2017
DOI: 10.1021/acs.jpcc.6b10860
|View full text |Cite
|
Sign up to set email alerts
|

How Density Functional Theory Surface Energies May Explain the Morphology of Particles, Nanosheets, and Conversion Films Based on Layered Double Hydroxides

Abstract: Conversion films based on layered double 13 hydroxides constitute an important and environmentally 14 friendly technology for the corrosion protection of aeronaut-15 ical structures. Unfortunately, the morphology of layered 16 double hydroxide (LDH) conversion films is still not well 17 understood. In the present work, the structure and driving 18 forces behind the morphology of zinc−aluminum LDH 19 conversion films on aluminum alloy 2024 (AA2024) are explained from the perspective of molecular modeling. Since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Zn2Al(OH)6-NO3) and the Zn2Al(OH)6-MBT LDH synthesized at pH = 10, thermogravimetric analysis (TGA) was also performed to obtain insights into the amount of water molecules inside the interlayers (Figures S3 and S11), which are analyzed in view of the results from the MD simulations discussed above. For the precursor, it is possible to find computational studies in the literature where one (Galvão et al, 2017) and, more commonly, two (Galvão et al, 2016b;Pérez-Sánchez et al, 2018) water molecules per nitrate anion yielded structures with interlayer spacings that are in good agreement with those estimated from the experimental XRD results. From the Zn2Al(OH)6-NO3 TGA results presented in the Supporting Information (Figures S3 and S11), the mass loss at T = 170 ºC is associated to the release of a single water molecule per anion, whereas the mass loss at T = 230 ºC corresponds to the release of two water molecules per anion.…”
Section: Correlations Between Experimental and Computational Datasupporting
confidence: 53%
See 1 more Smart Citation
“…Zn2Al(OH)6-NO3) and the Zn2Al(OH)6-MBT LDH synthesized at pH = 10, thermogravimetric analysis (TGA) was also performed to obtain insights into the amount of water molecules inside the interlayers (Figures S3 and S11), which are analyzed in view of the results from the MD simulations discussed above. For the precursor, it is possible to find computational studies in the literature where one (Galvão et al, 2017) and, more commonly, two (Galvão et al, 2016b;Pérez-Sánchez et al, 2018) water molecules per nitrate anion yielded structures with interlayer spacings that are in good agreement with those estimated from the experimental XRD results. From the Zn2Al(OH)6-NO3 TGA results presented in the Supporting Information (Figures S3 and S11), the mass loss at T = 170 ºC is associated to the release of a single water molecule per anion, whereas the mass loss at T = 230 ºC corresponds to the release of two water molecules per anion.…”
Section: Correlations Between Experimental and Computational Datasupporting
confidence: 53%
“…DFT calculations were also employed to analyze the morphology of ZnAl LDH conversion films on the aluminum alloy 2024, with the metal surface modelled with periodic Al(111) or -Al2O3(0001) slabs while the LDH considered a fragment with a single nitrate anion (Galvão et al, 2017). Galvão et al demonstrated Experimental data obtained in our laboratory or found in the literature were analyzed and discussed in the light of the results from the MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…1c. Morphology and crystallization process of Zn/Al-LDHs grown on Al substrates are comprehensively discussed in previous studies 11,42,43 . Some Zn/Al-LDH nanoplatelets were scraped from the Al foils and elemental composition analysis by means of energy dispersive X-ray spectroscopy (EDX) revealed an average Zn/Al ratio equal to about 2.0 for all the prepared LDH samples (a summary of EDX data is given in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Then, hydroxyl groups were added to the uppermost aluminum layer of the model until reaching a degree of hydroxylation of 75%, i.e., 3 hydroxyl groups per (2 × 2) supercell as suggested from the DFT studies in Ref. [27], and as applied in a previous work [28].…”
Section: Computational Sectionmentioning
confidence: 99%